Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure, let's break down the given polynomial \( P_3(x) \) step by step and then expand it fully to arrive at the simplified form.
The polynomial is given by:
[tex]\[ P_3(x) = 1 + (x+1) - \frac{2}{3}(x+1)(x-1) - \frac{1}{12}(x+1)(x-1)(x-2) \][/tex]
### Step-by-Step Expansion
1. Simplify each term separately:
- The first term is simply \( 1 \).
- The second term is \( (x + 1) \).
- The third term is \( - \frac{2}{3}(x+1)(x-1) \):
[tex]\[ (x + 1)(x - 1) = x^2 - 1 \][/tex]
Therefore:
[tex]\[ - \frac{2}{3}(x^2 - 1) = - \frac{2}{3}x^2 + \frac{2}{3} \][/tex]
- The fourth term is \( - \frac{1}{12}(x+1)(x-1)(x-2) \):
[tex]\[ (x + 1)(x - 1)(x - 2) = (x^2 - 1)(x - 2) = x^3 - 2x^2 - x + 2 \][/tex]
Therefore:
[tex]\[ -\frac{1}{12}(x^3 - 2x^2 - x + 2) = - \frac{1}{12}x^3 + \frac{1}{6}x^2 + \frac{1}{12}x - \frac{1}{6} \][/tex]
2. Combine all the terms together:
Summarize all the contributions from each term into \( P_3(x) \):
[tex]\[ P_3(x) = 1 + (x + 1) - \frac{2}{3}(x^2 - 1) - \frac{1}{12}(x^3 - 2x^2 - x + 2) \][/tex]
Substitute and combine:
[tex]\[ P_3(x) = 1 + x + 1 - \frac{2}{3}x^2 + \frac{2}{3} - \frac{1}{12}x^3 + \frac{1}{6}x^2 + \frac{1}{12}x - \frac{1}{6} \][/tex]
3. Combine all like terms:
- Constants:
[tex]\[ 1 + 1 + \frac{2}{3} - \frac{1}{6} = \frac{3}{3} + \frac{2}{3} - \frac{1}{6} = 2 + \frac{1}{6} = 2.5 \][/tex]
- \( x \) terms:
[tex]\[ x + \frac{1}{12}x = 1.08333333333333 x \][/tex]
- \( x^2 \) terms:
[tex]\[ -\frac{2}{3}x^2 + \frac{1}{6}x^2 = -\frac{4}{6}x^2 + \frac{1}{6}x^2 = - \frac{1}{2}x^2 \][/tex]
- \( x^3 \) terms:
[tex]\[ - \frac{1}{12}x^3 = -0.0833333333333333 x^3 \][/tex]
Final combined polynomial:
[tex]\[ P_3(x) = -0.0833333333333333 x^3 - 0.5 x^2 + 1.08333333333333 x + 2.5 \][/tex]
Therefore,
[tex]\[ P_3(x) = 1 + (x+1) - \frac{2}{3}(x+1)(x-1) - \frac{1}{12}(x+1)(x-1)(x-2) \][/tex]
expands and simplifies to:
[tex]\[ P_3(x) = -0.0833333333333333 x^3 - 0.5 x^2 + 1.08333333333333 x + 2.5 \][/tex]
The polynomial is given by:
[tex]\[ P_3(x) = 1 + (x+1) - \frac{2}{3}(x+1)(x-1) - \frac{1}{12}(x+1)(x-1)(x-2) \][/tex]
### Step-by-Step Expansion
1. Simplify each term separately:
- The first term is simply \( 1 \).
- The second term is \( (x + 1) \).
- The third term is \( - \frac{2}{3}(x+1)(x-1) \):
[tex]\[ (x + 1)(x - 1) = x^2 - 1 \][/tex]
Therefore:
[tex]\[ - \frac{2}{3}(x^2 - 1) = - \frac{2}{3}x^2 + \frac{2}{3} \][/tex]
- The fourth term is \( - \frac{1}{12}(x+1)(x-1)(x-2) \):
[tex]\[ (x + 1)(x - 1)(x - 2) = (x^2 - 1)(x - 2) = x^3 - 2x^2 - x + 2 \][/tex]
Therefore:
[tex]\[ -\frac{1}{12}(x^3 - 2x^2 - x + 2) = - \frac{1}{12}x^3 + \frac{1}{6}x^2 + \frac{1}{12}x - \frac{1}{6} \][/tex]
2. Combine all the terms together:
Summarize all the contributions from each term into \( P_3(x) \):
[tex]\[ P_3(x) = 1 + (x + 1) - \frac{2}{3}(x^2 - 1) - \frac{1}{12}(x^3 - 2x^2 - x + 2) \][/tex]
Substitute and combine:
[tex]\[ P_3(x) = 1 + x + 1 - \frac{2}{3}x^2 + \frac{2}{3} - \frac{1}{12}x^3 + \frac{1}{6}x^2 + \frac{1}{12}x - \frac{1}{6} \][/tex]
3. Combine all like terms:
- Constants:
[tex]\[ 1 + 1 + \frac{2}{3} - \frac{1}{6} = \frac{3}{3} + \frac{2}{3} - \frac{1}{6} = 2 + \frac{1}{6} = 2.5 \][/tex]
- \( x \) terms:
[tex]\[ x + \frac{1}{12}x = 1.08333333333333 x \][/tex]
- \( x^2 \) terms:
[tex]\[ -\frac{2}{3}x^2 + \frac{1}{6}x^2 = -\frac{4}{6}x^2 + \frac{1}{6}x^2 = - \frac{1}{2}x^2 \][/tex]
- \( x^3 \) terms:
[tex]\[ - \frac{1}{12}x^3 = -0.0833333333333333 x^3 \][/tex]
Final combined polynomial:
[tex]\[ P_3(x) = -0.0833333333333333 x^3 - 0.5 x^2 + 1.08333333333333 x + 2.5 \][/tex]
Therefore,
[tex]\[ P_3(x) = 1 + (x+1) - \frac{2}{3}(x+1)(x-1) - \frac{1}{12}(x+1)(x-1)(x-2) \][/tex]
expands and simplifies to:
[tex]\[ P_3(x) = -0.0833333333333333 x^3 - 0.5 x^2 + 1.08333333333333 x + 2.5 \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.